HUBUNGAN LAMA MENJALANI HEMODIALISIS DENGAN GANGGUAN KOGNITIF PADA PENDERITA PENYAKIT GINJAL KRONIS - , RUSTANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background. The prevalence of cognitive impairment in chronic kidney diseases occurs about 37% on 336 patients after two years haemodialisis treatment. Research on long-standing relationships undergoing hemodialysis with cognitive impairment has not been done in Indonesia. The aim of this reasearch is to determine about long-standing relationships undergoing hemodialysis with cognitive impairment. Methods. The method uses cross-sectional sudy. Research subjects obtained from chronic kidney disease patients undergoing hemodialysis at RSUP Dr. Sardjito Yogyakarta. Samples were taken in sequence and were interviewed using a structured questionnaire. Cognitive impairment using a measuring instrument Mini Mental State Examination (MMSE). Hypothesis testing bivariate analysis using Chi-square and ttest, while multivariate analysis using logistic regression. Results. The number of subjects who entered the study inclusion criteria of 64 subjects, consisting of 31 (48.4%) male subjects and 32 (51.6%) female subjects. Bivariate analysis was not significantly longer hemodialysis significant cognitive impairment with RP 0.625 (95% CI 0.365 to 1.166). Other variables which significant with cognitive impairment are anemia and hypotension during dialysis. The results of multivariate analysis significant independent variables significantly to cognitive impairment in order are hypotension during dialysis (95% CI, p = 0.001